Proceedings CLIMA 2022 The 14th REHVA HVAC World Congress - Itard, Laure; Hensen-Centnerová, Lada; Boerstra, Atze; Bluyssen, Philomena; Hensen, Jan; Klein, Tillmann; Loomans, Marcel; Pauwels, Pieter; Struck, Christian; Tenpierik, Martin; Geldermans, Bob (TU Delft Open, 2022)
The 14th REHVA HVAC World Congress CLIMA2022 challenges advances in technologies for smart energy transition, digitization, circularity, health and well-being in buildings. How can we create circular buildings, fully heated, cooled and powered by renewable energy? How can we design human-centered indoor environments while mastering life-cycle costs? How can we also include their integration into infrastructure for energy, health, data and education?